(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The goal of the project, being run by the Institute of Applied Geodesy of the Warsaw University of Technology, is to create a prototype database of building structures, which are typical from the point of view of the tasks of engineering geodesy.The database is expected to be available through the Internet and is planned to be filled with the information collected from surveying companies, which would like to present their realizations both from owners and users of engineering structures.Examples of modern solutions in the area of geodetic services for engineering investments realization is supposed to create a base for changes in the methods of teaching and presenting these issues at the Faculty of Geodesy and Cartography of the Warsaw University of Technology and at other Faculties interested in such problems.